Advances in allogeneic hematopoietic stem cell transplantation for Langerhans cell histiocytosis in children - Meng, Guangqiang; Feng, Saran; Wang, Yan (Frontiers in Immunology, 2025)
Langerhans cell histiocytosis (LCH) is a disease caused by clonal expansion of CD1a+/CD207+ cells and is characterized by organ involvement and dysfunction. Treatment of LCH in children is risk-adapted, and multisystem LCH requires systemic therapy. Although systemic treatments such as chemotherapy and BRAF/MEK inhibitors have improved the cure rate of LCH, disease reactivation rates remain 30%, and eventually some patients progress to relapse-refractory LCH. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a promising salvage treatment strategy for children with relapse-refractory LCH. However, many questions such as the efficacy and indications of allo-HSCT, as well as suitable conditioning regimen are still undetermined for children with LCH. This review aimed to provide an update on advances in allo-HSCT for LCH in children, including indications, stem cell sources, conditioning regimens, chimerism, transplant-related complications, outcomes, and treatment of relapse.